Pelatihan Peningkatan Kualitas Produk Ramuan Tradisional Kabupaten Bangli, Bali: Training for Improving the Quality of Traditional Herbal Products in Bangli Regency, Bali - Wahyuni, Tutik Sri; Widyowati, Retno; Purwitasari, Neny; Widyawaruyanti, Aty; Fuad, Achmad; Poerwono, Hadi; Isadiartuti, Dewi; Sulistyowaty, Melanny Ika; Yusuf, Helmy; Rudyanto, Marcellino; Kusumawati, Idha; Widiandani, Tri; Retnowati, Dini (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Bali is renowned as a tourist island rich in local wisdom, one of which is the traditional herbal remedy loloh cemcem from Penglipuran Village, Bangli Regency. This herbal drink has long been used to maintain health and alleviate internal heat. However, the loloh cemcem products produced by the local community still fall short of the standards for quality traditional medicine preparations, particularly in terms of product quality, packaging, and labeling. Through a community service initiative, activities such as observation, education, training, and mentoring were conducted for local entrepreneurs, focusing on proper selection of raw materials, hygienic production processes, safe packaging practices, accurate labeling of composition, and the implementation of Standard Operating Procedures (SOPs). The training, attended by more than 20 participants from MSMEs and youth organizations (karang taruna), aimed to enhance public understanding of the benefits and importance of high-quality herbal products. It is hoped that loloh cemcem can evolve into a safe, high-quality, efficacious, and competitive traditional beverage. Furthermore, product innovation may serve as an alternative strategy for developing loloh cemcem preparations and expanding their recognition among the wider public.